MULTI-BASIS WAVENET-BASED SPEED ESTIMATION IN DIRECT TORQUE CONTROLLED ASYNCHRONOUS MOTOR (Journal of Engineering, 2024)
This paper presents a proposed method for speed estimation of asynchronous motor in Direct Torque Control (DTC) system, based on a new architecture of multi-basis wavenet model. Such multi-basis model utilizes multi-set daughter wavelets. Firstly, the structure and training algorithm of the proposed method is discussed. The descent gradient method is used to fulfill both system structure and parameters initialization. Secondly, the proposed speed estimator and the DTC asynchronous motor are combined based on stator current signal and the motor speed is then estimated online with the operation of the system. Finally, the effectiveness of this method is proved by simulation carried out using Matlab/Simulink library and compared with the actual results obtained from the dynamic equations of the motor. The simulation results are obtained over the entire speed of starting, load conditions and motor braking. These results show that the proposed method is effective for speed estimation in DTC drives.